Preparation method and application of carbon dioxide electrocatalytic material with non-metallic element bulk phase-interface double doping

CN118531435BActive Publication Date: 2026-10-16ZHEJIANG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410670160.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2026-10-16
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

[0005]本发明的目的是针对现有氧化铜基催化剂价态不稳定、活性较低、电流效率较低、难掺杂等问题,提出了一种非金属元素体相-界面双重掺杂的二氧化碳电催化材料的制备方法及应用

Benefits of technology

[0019] This invention first adds boric acid during the preparation of cuprous oxide. Under alkaline conditions, boron is incorporated into the product, yielding a bulk boron-doped cuprous oxide precursor. The precursor is then subjected to vacuum plasma treatment to further optimize its surface. Argon gas is used to continuously introduce the boron dopant source into the reaction chamber, and plasma bombards the material surface with boron active particles, promoting bonding between boron and copper atoms. Boron atoms occupy some oxygen atom positions, resulting in uniform and stable doping. This process can further increase the boron doping amount in a short time, ultimately achieving dual optimization of the bulk and interface phases of the boron-doped cuprous oxide electrocatalyst, and preparing an electrocatalyst material with a high boron doping amount. The non-metallic element bulk-interface dual-doped carbon dioxide electrocatalyst provided by this invention can significantly increase the non-metallic element doping amount, exhibits excellent selectivity for the conversion of CO2RR to C2H4, and is beneficial to C… 2+ Product formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118531435B_ABST
    Figure CN118531435B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a non-metallic element bulk phase-interface double-doped carbon dioxide electrocatalytic material, first, boric acid is added in the process of preparing cuprous oxide, and boron elements are compounded into the product under alkaline conditions to obtain a bulk phase boron-doped cuprous oxide precursor; then, the precursor is subjected to vacuum plasma treatment to optimize the surface thereof, boron doping sources are continuously brought into a reaction chamber by using argon, and then boron active particles are made to bombard the surface of the material by using plasma so as to make boron atoms bond with copper atoms, the boron atoms occupy part of oxygen atom positions and are uniformly and stably doped into the material, and the boron element doping amount can be further improved in a short time, the bulk phase-interface double optimization of the boron-doped cuprous oxide electrocatalyst is realized, and the electrocatalytic material with a higher boron doping amount is prepared. 2+ The catalyst has excellent selectivity for the conversion of CO2RR into C2H4, and is beneficial to the generation of products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst preparation technology, specifically to the preparation method and application of carbon dioxide electrocatalytic materials with dual doping of non-metallic elements in bulk phase and interface. Background Technology

[0002] With rapid economic and population development, the excessive use of fossil fuels has led to a year-on-year increase in carbon dioxide (CO2) emissions, triggering a series of climate problems. Mitigating the impact of CO2 emissions has become a pressing issue. Electrocatalytic CO2 reduction reaction (CO2RR) can utilize renewable and clean electricity to convert CO2 into fuels and value-added feedstocks, such as ethylene and ethanol, which are multi-carbon products. It boasts advantages such as high conversion efficiency, mild reaction conditions, and ease of operation, making it a highly promising CO2 resource utilization pathway and offering a promising solution to the energy and environmental crisis.

[0003] Currently, among CO2 electroreduction catalysts, copper-based materials are favored due to their unique electronic properties and excellent C content. 2+ The product conversion ability has attracted much attention. Cu₂O is particularly beneficial for promoting CO₂ activation and CC coupling processes; however, Cu₂O is less effective in catalytic processes. + It is easily reduced to Cu at high negative potentials. 0 This significantly limits its widespread application. Research shows that by doping Cu₂O with non-metallic elements such as boron to replace the oxygen atoms in the lattice, the properties of Cu can be adjusted. + By optimizing the electronic structure of the sites and the adsorption of key intermediates, the catalytic conversion of CO2 to C can be improved. 2+ The properties of the product. However, boron atoms have a radius of 85 pm, which is larger than that of oxygen atoms, and their ionic valence states are different, resulting in low substitution doping levels. Existing one-step doping strategies often struggle to achieve high doping levels, such as Zhou Yansong [Zhou YS, Che FL, Liu M, et al. Dopant-induced electron localization drives CO2 reduction to C 2+ Hydrocarbons. Nature Chem 10, 974-980 (2018)] et al. prepared a Cu(B) catalyst using copper chloride via a simple one-step method, achieving a maximum B / Cu ratio of 2.2%. Yang Canyan [Yang CY, Wang RC, Yu C, et al. Engineering stable Cu + -Cu 0sites and oxygen defects in boron-doped copper oxide for electrocatalytic reduction of CO2 to C 2+ [products[J]. Chemical Engineering Journal, 484, 149710 (2024)] et al. prepared B-Cu by a simple one-step method x For O catalysts, the highest B / Cu ratio is 1.956%. Therefore, developing a catalyst preparation strategy with high boron doping remains both attractive and challenging. Summary of the Invention

[0004] This invention provides a method for preparing and applying a carbon dioxide electrocatalytic material with dual bulk-interface doping of non-metallic elements. The method improves the boron doping amount and alters the Cu content through dual optimization of the bulk-interface doping. + The electronic structure of the site promotes electron transport rate, lowers the formation energy barrier of key intermediates, and effectively improves C 2+ Product selectivity and conversion rate.

[0005] The purpose of this invention is to address the problems of unstable valence state, low activity, low current efficiency, and difficulty in doping existing copper oxide-based catalysts. It proposes a method for preparing and applying a non-metallic element-doped bulk-interface dual-doped carbon dioxide electrocatalytic material. By adding boric acid during the hydrothermal preparation of cuprous oxide, boron is incorporated into the product under alkaline conditions, resulting in a bulk boron-doped cuprous oxide precursor. This precursor is then subjected to vacuum plasma treatment to further optimize its surface. Argon gas is used to continuously introduce the boron dopant source into the reaction chamber, and plasma bombards the material surface with boron active particles, promoting bonding between boron and copper atoms. Boron atoms occupy some oxygen atom positions, resulting in uniform and stable doping of the material. Furthermore, the boron doping amount can be further increased in a short time, ultimately achieving bulk-interface dual optimization of the boron-doped cuprous oxide electrocatalyst and preparing an electrocatalytic material with a high boron doping content.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for preparing a carbon dioxide electrocatalytic material with non-metallic element bulk-interface dual doping, specifically including the following steps:

[0008] 1) Prepare a copper salt aqueous solution, add boric acid and ultrasonically mix. Heat the mixture in a water bath, then slowly add sodium hydroxide solution dropwise to the mixture at a uniform rate while stirring continuously for a period of time. Next, add ascorbic acid solution dropwise to the mixture while stirring continuously for a period of time. Separate the liquid from the precipitate and wash it several times with water and alcohol before drying to obtain the bulk boron-doped cuprous oxide catalyst (B). x -Cu2O).

[0009] 2) Add boric acid powder to the preheating furnace at the front end of the plasma-enhanced vapor deposition apparatus, and add the B obtained in step 1). x -Cu₂O was placed in a tubular slide rail furnace at the rear end of a plasma-enhanced vapor deposition apparatus, and vacuum was repeatedly applied. Argon was used as the carrier gas. After the preheating furnace and the tubular slide rail furnace were heated to a certain temperature, plasma treatment was performed to obtain the non-metallic element bulk-interface dual-doped cuprous oxide catalyst (B). x -Cu2O-yW).

[0010] Further, the concentration of the copper salt aqueous solution in step 1) is 0.001~0.1 mol / L, preferably 0.005~0.01 mol / L; the molar ratio of boric acid to copper salt is (0.05~1):1; the ultrasonic mixing time is 0.1~0.3 h, so that the two solutions are fully mixed and the bulk boron doping is more uniform; the water bath heating temperature is 40~60 ℃.

[0011] Further, the concentration of the sodium hydroxide solution in step 1) is 1~3 mol / L, the concentration of the ascorbic acid solution is 0.1~1 mol / L, and the molar ratio of copper salt, sodium hydroxide and ascorbic acid is 1:(10~30):(1~10), preferably 1:20:6;

[0012] Furthermore, in step 1), the dropping rate of sodium hydroxide and ascorbic acid is 1~5 mL / min. The slow and uniform dropping makes the catalyst nucleation more uniform. After the sodium hydroxide is added, the mixture is stirred for 0.1~1 h, and after the ascorbic acid is added, the mixture is stirred for 1~5 h.

[0013] Furthermore, the separation method described in step 1) employs centrifugal separation, with water washing and alcohol washing performed 1 to 3 times each, and ultrasonication for 1 to 5 minutes before each centrifugation to thoroughly wash away residual impurities on the catalyst surface; vacuum freeze drying is employed, which is more conducive to the evaporation of residual solvents in the micropores of the catalyst material and better preserves the crystal morphology of the catalyst.

[0014] Furthermore, the boron doping source described in step 2) and B x The mass ratio of Cu₂O is (1~3):1.

[0015] Furthermore, the heating rate of the preheating furnace described in step 2) is 1~10 ℃ / min, from room temperature to 250~350℃; the heating rate of the tubular slide rail furnace is 1~5 ℃ / min, from room temperature to 40~60℃, to activate the surface activity of the material. The temperature should not be too high, otherwise it will seriously damage the material structure.

[0016] Furthermore, in step 2), the plasma generator power is 100~300 W and the processing time is 0.1~0.5 h during the plasma treatment.

[0017] This invention also provides the conversion of the non-metallic element-doped carbon dioxide electrocatalytic material to C in CO2RR (carbon dioxide reduction reaction). 2+ Application of the product (multi-carbon product). The specific application method is as follows: carbon paper coated with the electrocatalytic material is used as the cathode, Pt sheet is used as the anode, saturated Ag / AgCl electrode is used as the reference electrode, and CO2-saturated 0.1~1mol / L KHCO3 aqueous solution is used as the electrolyte. The catalytic reaction is carried out in a flow cell. The product is collected for 15 seconds and then passed into the gas phase. The product Faraday efficiency is calculated based on the peak position and area.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] This invention first adds boric acid during the preparation of cuprous oxide. Under alkaline conditions, boron is incorporated into the product, yielding a bulk boron-doped cuprous oxide precursor. The precursor is then subjected to vacuum plasma treatment to further optimize its surface. Argon gas is used to continuously introduce the boron dopant source into the reaction chamber, and plasma bombards the material surface with boron active particles, promoting bonding between boron and copper atoms. Boron atoms occupy some oxygen atom positions, resulting in uniform and stable doping. This process can further increase the boron doping amount in a short time, ultimately achieving dual optimization of the bulk and interface phases of the boron-doped cuprous oxide electrocatalyst, and preparing an electrocatalyst material with a high boron doping amount. The non-metallic element bulk-interface dual-doped carbon dioxide electrocatalyst provided by this invention can significantly increase the non-metallic element doping amount, exhibits excellent selectivity for the conversion of CO2RR to C2H4, and is beneficial to C… 2+ Product formation.

[0020] The method of this invention is simple, low-cost, green, and controllable; by adding different amounts of boric acid during the synthesis of cuprous oxide, bulk boron-doped cuprous oxide (B₂O₃) with different doping levels and smaller particle sizes can be obtained. x -Cu2O); then, vacuum plasma technology is used to bombard the material surface with boron active particles, promoting boron-copper bonding and ensuring that boron atoms are uniformly and stably incorporated into B. xIn Cu₂O, the low doping level of the one-step hydrothermal synthesis method was overcome, increasing the boron doping amount and further promoting the transfer of local electrons to non-metallic elements, thus altering Cu… + The electronic structure of the site thus protects the Cu-O bond and stabilizes Cu during the catalytic reduction reaction. + The active sites promote CO2 activation and reduce the energy barrier for CC coupling. The electrocatalytic material has smaller particle size, larger specific surface area and surface roughness, exposing more active sites, thus enhancing the activation of C2H4 and C2H4 in CO2RR. 2+ The selectivity of the product is improved, and the hydrogen evolution reaction is significantly suppressed. The electrocatalyst material prepared in this invention has a Faradaic efficiency of approximately 30% for the reduction of CO2 to ethylene, which is about 2.5 times higher than that of undoped cuprous oxide electrocatalyst for the reduction of CO2 to ethylene. Attached Figure Description

[0021] Figure 1 Cu2O and B prepared in the control example, Example 2, and Example 5, respectively. 0.25 -Cu2O, B 0.25 SEM image of the Cu2O-200W electrocatalytic material sample.

[0022] Figure 2 B prepared in Examples 2 and 5 respectively 0.25 -Cu2O and B 0.25 XPS spectra of B1s of the Cu2O-200W electrocatalytic material sample.

[0023] Figure 3 The electrocatalytic materials prepared in the control example and the example respectively catalyze the electrocatalytic conversion of CO2 to C. 2+ A comparison chart of Faraday efficiency between C2H4 and C2H4. Detailed Implementation

[0024] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0025] Comparison Example

[0026] The control example was undoped cuprous oxide. 241.6 mg of copper nitrate trihydrate was weighed and added to ultrapure water to prepare 100 mL of a 0.01 mol / L copper nitrate solution. The prepared copper nitrate solution was poured into a beaker and sonicated for 10 min, then transferred to a 55 °C water bath for heating and stirring. 4.0 g of sodium hydroxide powder was weighed and prepared into 50 mL of a 2.0 mol / L sodium hydroxide aqueous solution. After the water bath temperature stabilized, 10 mL of the sodium hydroxide aqueous solution was slowly added dropwise to the above solution at a rate of 1 mL / min. After stirring continuously for 30 min, 5.28 g of ascorbic acid powder was weighed and prepared into 50 mL of a 0.6 mol / L ascorbic acid aqueous solution. 10 mL of the ascorbic acid aqueous solution was slowly added dropwise to the above solution at a rate of 1 mL / min. After the addition was completed, the reaction was continued for 3 h under water bath heating and continuous stirring. The precipitate was separated by centrifugation, washed three times with ultrapure water and twice with ethanol to obtain a brick-red precipitate, which was then freeze-dried at -50 °C for 12 h to obtain ordinary cuprous oxide electrocatalytic material (Cu2O).

[0027] The cuprous oxide electrocatalyst Cu2O prepared in the control example was analyzed by SEM, such as... Figure 1 The cuprous oxide shown in figure a has a smooth cubic structure with a particle size of approximately 800 nm.

[0028] Electrocatalytic performance of the cuprous oxide electrocatalytic material Cu2O prepared in the control example was tested:

[0029] Weigh 15 mg of cuprous oxide electrocatalyst material and put it into a sample vial. Add 1275 μL of isopropanol, 150 μL of ultrapure water and 75 μL of 5% Nafion, mix and add ice packs and sonicate for 1 h to finally obtain a uniformly dispersed catalyst ink.

[0030] The catalyst ink prepared above was poured into a spray gun and evenly sprayed onto a 1*3 cm carbon paper placed on a heated plate. The mass of the sprayed catalyst was approximately 3 mg. The carbon paper with the catalyst was used as the cathode, a Pt sheet as the anode, and an Ag / AgCl electrode as the reference electrode. Catalytic performance was tested using a Wuhan KOST CS2350H electrochemical workstation. The catalytic reaction was carried out in a flow cell, and the electrolyte was a CO2-saturated 0.1–1 mol / L KHCO3 aqueous solution. A constant potential polarization of -1.84 V (vsAg / AgCl) was used, and the products were collected and detected by gas phase analysis. The corresponding Faradaic efficiency was calculated based on the peak position and area. The electrocatalytic performance of ordinary cuprous oxide in the control example showed a total current density of 47.3 mA, an ethylene Faradaic efficiency of 13.2%, and a bias current density of 6.24 mA. 2+The product has a Faraday efficiency of 23.2% and a bias current density of 10.97 mA.

[0031] Example 1

[0032] The difference from the comparative example is that boric acid powder was added during the preparation process, and the molar ratio of boric acid to copper salt was 0.05:1. Specifically, 241.6 mg of copper nitrate trihydrate was weighed and added to ultrapure water to prepare 100 mL of 0.01 mol / L copper nitrate solution. 3.09 mg of boric acid powder was weighed and added to the prepared copper nitrate solution and sonicated for 10 min. Then, the solution was transferred to a 55 °C water bath for heating and stirring. 4.0 g of sodium hydroxide powder was weighed and prepared to prepare 50 mL of 2.0 mol / L sodium hydroxide aqueous solution. After the water bath temperature stabilized, 10 mL of the sodium hydroxide aqueous solution was slowly added dropwise to the above solution at a rate of 1 mL / min. After stirring continuously for 30 min, 5.28 g of ascorbic acid powder was weighed and prepared to prepare 50 mL of 0.6 mol / L ascorbic acid aqueous solution. 10 mL of the ascorbic acid aqueous solution was slowly added dropwise to the above solution at a rate of 1 mL / min. After the addition was completed, the reaction was continued for 3 h under water bath heating and continuous stirring. The precipitate was separated by centrifugation, washed three times with ultrapure water and twice with ethanol to obtain a brick-colored precipitate, which was then freeze-dried at -50 °C for 12 h to obtain the bulk boron-doped cuprous oxide electrocatalyst B. 0.05 -Cu2O.

[0033] Example 1 shows the preparation of bulk boron-doped cuprous oxide electrocatalytic material B. 0.05 Electrocatalytic performance testing of Cu2O:

[0034] Weigh out 15 mg of B 0.05 - The Cu2O electrocatalytic material was loaded into a sample vial, and 1275 μL of isopropanol, 150 μL of ultrapure water and 75 μL of 5% Nafion were added and mixed. The mixture was then sonicated with an ice pack for 1 h to obtain a uniformly dispersed catalyst ink.

[0035] The catalyst ink prepared above was poured into a spray gun and evenly sprayed onto a 1*3 cm carbon paper placed on a heated plate. The mass of the sprayed catalyst was approximately 3 mg. The carbon paper with the sprayed catalyst was used as the cathode, a Pt sheet as the anode, and an Ag / AgCl electrode as the reference electrode. Catalytic performance was tested using a Wuhan KOST CS2350H electrochemical workstation. The catalytic reaction was carried out in a flow cell, and the electrolyte was a CO2-saturated 0.1~1 mol / L KHCO3 aqueous solution. A constant potential polarization of -1.84 V (vs Ag / AgCl) was used, and the products were collected and detected by gas chromatography. The corresponding Faraday efficiency was calculated based on the peak position and area. Example 1 prepared B 0.05 The electrocatalytic performance of Cu₂O showed a total current density of 49.8 mA, an ethylene Faradaic efficiency of 18.01%, and a partial current density of 8.97 mA; C 2+ The product has a Faraday efficiency of 29.03% and a partial current density of 14.46 mA.

[0036] Example 2

[0037] The difference from the comparative example is that boric acid powder was added during the preparation process, and the molar ratio of boric acid to copper salt was 0.25:1. Specifically, 241.6 mg of copper nitrate trihydrate was weighed and added to ultrapure water to prepare 100 mL of 0.01 mol / L copper nitrate solution. 15.45 mg of boric acid powder was weighed and added to the prepared copper nitrate solution and sonicated for 10 min. Then, the solution was transferred to a 55 °C water bath for heating and stirring. 4.0 g of sodium hydroxide powder was weighed and prepared into 50 mL of 2.0 mol / L sodium hydroxide aqueous solution. After the water bath temperature stabilized, 10 mL of the sodium hydroxide aqueous solution was slowly added dropwise to the above solution at a rate of 1 mL / min. After stirring continuously for 30 min, 5.28 g of ascorbic acid powder was weighed and a 50 mL 0.6 mol / L ascorbic acid aqueous solution was prepared. 10 mL of the ascorbic acid aqueous solution was slowly added dropwise to the above solution at a rate of 1 mL / min. After the addition was complete, the reaction was continued for 3 h under water bath heating and continuous stirring. The precipitate was separated by centrifugation, washed three times with ultrapure water and twice with ethanol to obtain a deep orange-red precipitate. This precipitate was freeze-dried at -50 °C for 12 h to obtain the bulk boron-doped cuprous oxide electrocatalyst material B. 0.25 -Cu2O.

[0038] Example 2 shows the preparation of bulk boron-doped cuprous oxide electrocatalytic material B. 0.25 -Cu2O was analyzed by SEM, such as Figure 1 As shown in b, the bulk boron-doped cuprous oxide still has a cubic structure, but the particle size is smaller, increasing the specific surface area of ​​the material. Figure 2As shown in Figure a, the successful boron doping can be seen from the B1s spectrum of the material's XPS, with a B / Cu ratio of 1.26%.

[0039] Example 2 shows the preparation of bulk boron-doped cuprous oxide electrocatalytic material B. 0.25 Electrocatalytic performance testing of Cu2O:

[0040] Weigh out 15 mg of B 0.25 - The Cu2O electrocatalytic material was loaded into a sample vial, and 1275 μL of isopropanol, 150 μL of ultrapure water and 75 μL of 5% Nafion were added and mixed. The mixture was then sonicated with an ice pack for 1 h to obtain a uniformly dispersed catalyst ink.

[0041] The catalyst ink prepared above was poured into a spray gun and evenly sprayed onto a 1*3 cm carbon paper placed on a heated plate. The mass of the sprayed catalyst was approximately 3 mg. The carbon paper with the sprayed catalyst was used as the cathode, a Pt sheet as the anode, and an Ag / AgCl electrode as the reference electrode. Catalytic performance was tested using a Wuhan KOST CS2350H electrochemical workstation. The catalytic reaction was carried out in a flow cell, and the electrolyte was a CO2-saturated 0.1–1 mol / L KHCO3 aqueous solution. A constant potential polarization of -1.84 V (vs Ag / AgCl) was used, and the products were collected and detected by gas chromatography. The corresponding Faraday efficiency was calculated based on the peak position and area. Example 2 prepared B 0.25 The total current density of Cu2O electrocatalysis was 58.3 mA, the ethylene Faradaic efficiency was 21.06%, and the partial current density was 12.28 mA; C 2+ The product has a Faraday efficiency of 32.64% and a partial current density of 19.03 mA.

[0042] Example 3

[0043] The difference from the comparative example is that boric acid powder was added during the preparation process, and the molar ratio of boric acid to copper salt was 0.5:1. Specifically, 241.6 mg of copper nitrate trihydrate was weighed and added to ultrapure water to prepare 100 mL of 0.01 mol / L copper nitrate solution. 30.9 mg of boric acid powder was weighed and added to the prepared copper nitrate solution and sonicated for 10 min. Then, the solution was transferred to a 55 °C water bath for heating and stirring. 4.0 g of sodium hydroxide powder was weighed and prepared into 50 mL of 2.0 mol / L sodium hydroxide aqueous solution. After the water bath temperature stabilized, 10 mL of the sodium hydroxide aqueous solution was slowly added dropwise to the above solution at a rate of 1 mL / min. After stirring continuously for 30 min, 5.28 g of ascorbic acid powder was weighed and prepared into 50 mL of 0.6 mol / L ascorbic acid aqueous solution. 10 mL of the ascorbic acid aqueous solution was slowly added dropwise to the above solution at a rate of 1 mL / min. After the addition was completed, the reaction was continued for 3 h under water bath heating and continuous stirring. The precipitate was separated by centrifugation, washed three times with ultrapure water and twice with ethanol to obtain a deep orange-red precipitate, which was then freeze-dried at -50 °C for 12 h to obtain the bulk boron-doped cuprous oxide electrocatalyst B. 0.5 -Cu2O.

[0044] Example 3 shows the preparation of bulk boron-doped cuprous oxide electrocatalyst material B. 0.5 Electrocatalytic performance testing of Cu2O:

[0045] Weigh out 15 mg of B 0.5 - The Cu2O electrocatalytic material was loaded into a sample vial, and 1275 μL of isopropanol, 150 μL of ultrapure water and 75 μL of 5% Nafion were added and mixed. The mixture was then sonicated with an ice pack for 1 h to obtain a uniformly dispersed catalyst ink.

[0046] The catalyst ink prepared above was poured into a spray gun and evenly sprayed onto a 1*3 cm carbon paper placed on a heated plate. The mass of the sprayed catalyst was approximately 3 mg. The carbon paper with the sprayed catalyst was used as the cathode, a Pt sheet as the anode, and an Ag / AgCl electrode as the reference electrode. Catalytic performance was tested using a Wuhan KOST CS2350H electrochemical workstation. The catalytic reaction was carried out in a flow cell, and the electrolyte was a CO2-saturated 0.1–1 mol / L KHCO3 aqueous solution. A constant potential polarization of -1.84 V (vs Ag / AgCl) was used, and the products were collected and detected by gas chromatography. The corresponding Faraday efficiency was calculated based on the peak position and area. Example 3 prepared B... 0.5 The electrocatalytic performance of Cu₂O showed a total current density of 51.4 mA, an ethylene Faradaic efficiency of 16.15%, and a partial current density of 8.30 mA; C2+ The product has a Faraday efficiency of 27.37% and a partial current density of 14.07 mA.

[0047] Example 4

[0048] The difference from the comparative example is that the bulk boron-doped cuprous oxide electrocatalyst B prepared in Example 1... 0.05 -Cu2O underwent further surface optimization. Specifically: 150 mg of B prepared in Example 1 was weighed... 0.05 Cu₂O was evenly spread in a ceramic boat and placed in the tubular slide rail furnace at the rear of the plasma-enhanced vapor deposition (PEVD) apparatus. The target temperature was set to 60 °C, and the heating rate was 1.0 °C / min. Then, 300 mg of boric acid powder was weighed and evenly spread in the ceramic boat and placed in the preheating furnace at the front of the PPVD apparatus. The target temperature was set to 330 °C, and the heating rate was 10.0 °C / min. Argon was used as the carrier gas, and the entire PPVD apparatus was evacuated 3-4 times. Then, the preheating furnace and the tubular slide rail furnace were simultaneously turned on. After reaching the target temperature, the plasma generator was turned on at 200 W. After 15 min, the plasma generator was turned off, and the surface catalyst in the ceramic boat was collected, yielding boron-doped cuprous oxide material B (both bulk and interfacial). 0.05 -Cu2O-200W.

[0049] Example 4: Boron-doped cuprous oxide material B (bulk-interface dual doping) 0.05 Electrocatalytic performance testing of Cu2O-200W:

[0050] Weigh out 15 mg of B 0.05 - The Cu2O-200W electrocatalytic material was loaded into a sample vial, and 1275 μL of isopropanol, 150 μL of ultrapure water and 75 μL of 5% Nafion were added and mixed. The mixture was then sonicated with an ice pack for 1 h to obtain a uniformly dispersed catalyst ink.

[0051] The catalyst ink prepared above was poured into a spray gun and evenly sprayed onto a 1*3 cm carbon paper placed on a heated plate. The mass of the sprayed catalyst was approximately 3 mg. The carbon paper with the sprayed catalyst was used as the cathode, a Pt sheet as the anode, and an Ag / AgCl electrode as the reference electrode. Catalytic performance was tested using a Wuhan KOST CS2350H electrochemical workstation. The catalytic reaction was carried out in a flow cell, and the electrolyte was a CO2-saturated 0.1~1 mol / L KHCO3 aqueous solution. A constant potential polarization of -1.84 V (vs Ag / AgCl) was used, and the products were collected and detected by gas chromatography. The corresponding Faraday efficiency was calculated based on the peak position and area. Example 4 prepared B... 0.05The Cu2O-200W electrocatalytic performance showed a total current density of 58.5 mA, an ethylene Faradaic efficiency of 27.05%, and a partial current density of 15.82 mA; C 2+ The product has a Faraday efficiency of 38.15% and a partial current density of 22.32 mA.

[0052] Example 5

[0053] The difference from the comparative example is that the bulk boron-doped cuprous oxide electrocatalyst B prepared in Example 2... 0.25 -Cu2O underwent further surface optimization. Specifically: 150 mg of B prepared in Example 2 was weighed out. 0.25 Cu₂O was evenly spread in a ceramic boat and placed in the tubular slide rail furnace at the rear of the plasma-enhanced vapor deposition (PEVD) apparatus. The target temperature was set to 60 °C, and the heating rate was 1.0 °C / min. Then, 300 mg of boric acid powder was weighed and evenly spread in the ceramic boat and placed in the preheating furnace at the front of the PPVD apparatus. The target temperature was set to 330 °C, and the heating rate was 10.0 °C / min. Argon was used as the carrier gas, and the entire PPVD apparatus was evacuated 3-4 times. Then, the preheating furnace and the tubular slide rail furnace were simultaneously turned on. After reaching the target temperature, the plasma generator was turned on at 200 W. After 15 min, the plasma generator was turned off, and the surface catalyst in the ceramic boat was collected, yielding boron-doped cuprous oxide material B (both bulk and interfacial). 0.25 -Cu2O-200W.

[0054] Example 5: Boron-doped cuprous oxide material B (bulk-interface dual doping) 0.25 SEM analysis was performed using Cu2O-200W, such as... Figure 1 As shown in Figure c, the boron-doped cuprous oxide with dual bulk-interface doping still exhibits a cubic structure, but the surface roughness of the material structure is significantly increased. For example... Figure 2 As shown in b, the XPS B 1s spectrum of the material shows that boron doping was successfully achieved, and... Figure 2 Compared to a, bulk-interface co-doping can significantly increase the doping amount of non-metallic boron, with a B / Cu ratio of 6.35%.

[0055] Example 5: Boron-doped bulk-interface cuprous oxide material B 0.25 Electrocatalytic performance testing of Cu2O-200W:

[0056] Weigh out 15 mg of B 0.25- The Cu2O-200W electrocatalytic material was loaded into a sample vial, and 1275 μL of isopropanol, 150 μL of ultrapure water and 75 μL of 5% Nafion were added and mixed. The mixture was then sonicated with an ice pack for 1 h to obtain a uniformly dispersed catalyst ink.

[0057] The catalyst ink prepared above was poured into a spray gun and evenly sprayed onto a 1*3 cm carbon paper placed on a heated plate. The mass of the sprayed catalyst was approximately 3 mg. The carbon paper with the sprayed catalyst was used as the cathode, a Pt sheet as the anode, and an Ag / AgCl electrode as the reference electrode. Catalytic performance was tested using a Wuhan KOST CS2350H electrochemical workstation. The catalytic reaction was carried out in a flow cell, and the electrolyte was a CO2-saturated 0.1–1 mol / L KHCO3 aqueous solution. A constant potential polarization of -1.84 V (vs Ag / AgCl) was used, and the products were collected and detected by gas chromatography. The corresponding Faraday efficiency was calculated based on the peak position and area. Example 5 prepared B... 0.25 The electrocatalytic performance of Cu2O-200W was characterized by a total current density of 68.7 mA, an ethylene Faradaic efficiency of 30.21%, and a partial current density of 21.44 mA; C 2+ The product has a Faraday efficiency of 41.91% and a partial current density of 28.79 mA.

[0058] Example 6

[0059] The difference from the comparative example is that the bulk boron-doped cuprous oxide electrocatalyst B prepared in Example 3... 0.5 -Cu2O underwent further surface optimization. Specifically: 150 mg of B prepared in Example 3 was weighed out. 0.5 Cu₂O was evenly spread in a ceramic boat and placed in the tubular slide rail furnace at the rear of the plasma-enhanced vapor deposition (PEVD) apparatus. The target temperature was set to 60 °C, and the heating rate was 1.0 °C / min. Then, 300 mg of boric acid powder was weighed and evenly spread in the ceramic boat and placed in the preheating furnace at the front of the PPVD apparatus. The target temperature was set to 330 °C, and the heating rate was 10.0 °C / min. Argon was used as the carrier gas, and the entire PPVD apparatus was evacuated 3-4 times. Then, the preheating furnace and the tubular slide rail furnace were simultaneously turned on. After reaching the target temperature, the plasma generator was turned on at 200 W. After 15 min, the plasma generator was turned off, and the surface catalyst in the ceramic boat was collected, yielding boron-doped cuprous oxide material B (both bulk and interfacial). 0.5 -Cu2O-200W.

[0060] Example 6: Boron-doped cuprous oxide material B (bulk-interface dual doping) 0.5Electrocatalytic performance testing of Cu2O-200W:

[0061] Weigh out 15 mg of B 0.5 - The Cu2O-200W electrocatalytic material was loaded into a sample vial, and 1275 μL of isopropanol, 150 μL of ultrapure water and 75 μL of 5% Nafion were added and mixed. The mixture was then sonicated with an ice pack for 1 h to obtain a uniformly dispersed catalyst ink.

[0062] The catalyst ink prepared above was poured into a spray gun and evenly sprayed onto a 1*3 cm carbon paper placed on a heated plate. The mass of the sprayed catalyst was approximately 3 mg. The carbon paper with the catalyst was used as the cathode, a Pt sheet as the anode, and an Ag / AgCl electrode as the reference electrode. Catalytic performance was tested using a Wuhan KOST CS2350H electrochemical workstation. The catalytic reaction was carried out in a flow cell, and the electrolyte was a CO2-saturated 0.1~1 mol / L KHCO3 aqueous solution. A constant potential polarization of -1.84 V (vs Ag / AgCl) was used, and the products were collected and detected by gas chromatography. The corresponding Faraday efficiency was calculated based on the peak position and area. Example 6 prepared B... 0.5 The Cu2O-200W electrocatalytic performance showed a total current density of 60.3 mA, an ethylene Faradaic efficiency of 25.58%, and a partial current density of 15.42 mA; C 2+ The product has a Faraday efficiency of 36.29% and a partial current density of 21.88 mA.

[0063] The above description is a list of some implementation forms of the inventive concept and is not intended to limit the present invention in any way. Any modifications, equivalent changes, improvements, etc., made within the spirit and principles of the present invention shall still be included within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a carbon dioxide electrocatalytic material with non-metallic element bulk-interface dual doping, characterized in that, Includes the following steps: 1) Prepare a copper salt aqueous solution, add boric acid and ultrasonically mix. Heat the mixture in a water bath, then add sodium hydroxide aqueous solution dropwise while stirring continuously. Next, add ascorbic acid solution dropwise while stirring continuously. Afterward, separate the liquid from the precipitate and wash it several times with water and alcohol before drying to obtain bulk boron-doped cuprous oxide catalyst, i.e., B. x -Cu2O; 2) Add boric acid powder to the preheating furnace at the front end of the plasma-enhanced vapor deposition apparatus, and add the B obtained in step 1). x -Cu2O is placed in the tubular slide rail furnace at the back end of the plasma-enhanced vapor deposition device, and vacuum is drawn multiple times. Argon is used as the carrier gas. After the preheating furnace and the tubular slide rail furnace are heated, plasma treatment is performed to obtain a carbon dioxide electrocatalytic material with dual doping of non-metallic elements in bulk phase and interface. The boric acid powder and B x The mass ratio of Cu₂O is (1~3):1; During plasma treatment, the plasma generator power is 100~300 W, and the treatment time is 0.1~0.5 h; The heating rate of the preheating furnace is 1~10 ℃ / min, from ambient temperature to 250~350 ℃; The heating rate of the tubular slide rail furnace is 1~5 ℃ / min, from ambient temperature to 40~60 ℃.

2. The preparation method according to claim 1, characterized in that, In step 1), the concentration of the copper salt aqueous solution is 0.001~0.1 mol / L; The molar ratio of boric acid to copper salt is (0.01~1):1; The ultrasonic mixing time is 0.1~0.3 h; The water bath heating temperature is 40~60 ℃.

3. The preparation method according to claim 1, characterized in that, In step 1), the concentration of the sodium hydroxide aqueous solution is 1~3 mol / L; The concentration of the ascorbic acid solution is 0.1~1 mol / L; The molar ratio of copper salt, sodium hydroxide and ascorbic acid is 1:(10~30):(1~10).

4. The preparation method according to claim 1, characterized in that, In step 1), the dropping rate of both the sodium hydroxide aqueous solution and the ascorbic acid solution is 1~5 mL / min; After the sodium hydroxide is added, stir for 0.1 to 1 h, and after the ascorbic acid is added, stir for 1 to 5 h.

5. The preparation method according to claim 1, characterized in that, In step 1), the separation is performed by centrifugation, and the number of water washing and alcohol washing cycles is 1 to 3. Vacuum freeze drying is used for drying.

6. The application of the non-metallic element bulk-interface dual-doped carbon dioxide electrocatalytic material prepared by the preparation method according to any one of claims 1 to 5 in the carbon dioxide reduction reaction.

7. The application according to claim 6, characterized in that, include: Carbon paper coated with the non-metallic element bulk-interface dual-doped carbon dioxide electrocatalytic material was used as the cathode, Pt sheet as the anode, saturated Ag / AgCl electrode as the reference electrode, and CO2-saturated 0.1~1 mol / L KHCO3 aqueous solution as the electrolyte. The catalytic reaction was carried out in a flow cell.

Citation Information

Patent Citations

  • Non-metal doped copper-based catalytic material for electrocatalytic reduction of carbon dioxide as well as preparation method and application of non-metal doped copper-based catalytic material

    CN115710724A

  • Preparation method and application of carbon dioxide electrochemical reduction boron-doped cuprous oxide catalyst

    CN117802524A

  • Boron-doped copper catalysts for efficient conversion of co2 to multi-carbon hydrocarbons and associated methods

    US20210292924A1